Methylation analysis of DNA repair genes in Alzheimer's disease. (January 2017) - Coppedè, Fabio; Tannorella, Pierpaola; Stoccoro, Andrea; Chico, Lucia; Siciliano, Gabriele; Bonuccelli, Ubaldo; Migliore, Lucia
Highlights: DNA repair mechanisms are often impaired in Alzheimer's disease tissues. We investigated the methylation status of a panel of DNA repair genes in blood DNA of Alzheimer's disease (AD) individuals and matched controls. All the investigated genes resulted hypomethylated in both AD and control DNA. None of the genes that we investigated is likely to represent a peripheral epigenetic biomarker of AD. Abstract: There is substantial evidence of impaired DNA repair activities in Alzheimer's disease (AD) neurons and peripheral tissues, inducing some investigators to speculate that this could partially result from promoter hypermethylation of DNA repair genes, resulting in gene silencing in those tissues. In the present study a screening cohort composed by late-onset AD (LOAD) patients and healthy matched controls was evaluated with a commercially available DNA methylation array for the assessment of the methylation levels of a panel of 22 genes involved in major DNA repair pathways in blood DNA. We then applied a cost-effective PCR based methylation-sensitive high-resolution melting (MS-HRM) technique, in order to evaluate the promoter methylation levels of the following DNA repair genes: OGG1, PARP1, MRE11A, BRCA1, MLH1, and MGMT . The analysis was performed in blood DNA from 56 LOAD patients and 55 matched controls, including the samples previously assessed with the DNA methylation array as validating samples. Both approaches revealed that all the investigated genes were largely hypomethylated in LOAD and control blood DNA, and no difference between groups was observed. Collectively, present data do not support an increased promoter methylation of some of the major DNA repair genes in blood DNA of AD patients.